Monster manual (Wizards of the Coast LLC, 2025)
"This revised and expanded Monster Manual® contains a horde of creatures for the fifth edition Dungeons & Dragons game -- a monstrous menagerie of familiar favorites like dragons, giants, and mind flayers, plus a host of new monsters like the arch-hag and the blob of annihilation. Populate your worlds and adventures with the hundreds of monsters provided, and let their stories, illustrations, and easy-to-use stat blocks fuel your D&D® adventures for years to come." --Back cover.